The Effect of Using the Barman Model of the Development of Creative Thinking Skills in Physic Subject of the tenth Class Female Pupils of Hight Schools - Zhin Hameed Hama salh; Waad Muhamad Najat; Walla Gazy Mahmud (QALAAI ZANIST JOURNAL, 2022)
The current research aims to identify the effect of using the Barman model in developing innovative thinking skills for tenth-grade students in physics. Built by it in (1966). The researcher used the experimental method in order to achieve the goal of the research. The experiment was conducted from the first semester of the academic year (2020-2021), The researcher chose (Gazang high school for girls) in the Erbil governorate center to apply the experiment. The research sample was limited to (45) with (23) female students for the experimental group, and (22) female students for the control group. The two groups were rewarded in the variables (chronological age calculated in months, academic achievement of the parents, The achievement scores of science for all for the ninth grade of the school year (2019-2020), the general average of the grades of female students for the ninth grade of the academic year (2019-2020), the degree of intelligence, the test of innovative thinking skills, The researcher adopted the experimental design with partial control, with a pre and posttest for the two research groups. The experiment began on (10/2/2021) and continued until the day (1/4/2021). After completing the experiment, the results were statistically analyzed using the t-test for two independent samples. .test the results showed the superiority of the experimental group who studied using the Barman model over the students of the control group who studied in the usual way in developing innovative thinking.